Functional identification of the terpene synthase family involved in diterpenoid alkaloids biosynthesis in Aconitum carmichaelii - Liuying Mao; Baolong Jin; Lingli Chen; Mei Tian; Rui Ma; Biwei Yin; Haiyan Zhang; Juan Guo; Jinfu Tang; Tong Chen; Changjiangsheng Lai; Guanghong Cui; et al. (Elsevier, 2021)
Aconitum carmichaelii is a high-value medicinal herb widely used across China, Japan, and other Asian countries. Aconitine-type diterpene alkaloids (DAs) are the characteristic compounds in Aconitum. Although six transcriptomes, based on short-read next generation sequencing technology, have been reported from the Aconitum species, the terpene synthase (TPS) corresponding to DAs biosynthesis remains unidentified. We apply a combination of Pacbio isoform sequencing and RNA sequencing to provide a comprehensive view of the A. carmichaelii transcriptome. Nineteen TPSs and five alternative splicing isoforms belonging to TPS-b, TPS-c, and TPS-e/f subfamilies were identified. In vitro enzyme reaction analysis functional identified two sesqui-TPSs and twelve diTPSs. Seven of the TPS-c subfamily genes reacted with GGPP to produce the intermediate ent-copalyl diphosphate. Five AcKSLs separately reacted with ent-CPP to produce ent-kaurene, ent-atiserene, and ent-13-epi-sandaracopimaradie: a new diterpene found in Aconitum. AcTPSs gene expression in conjunction DAs content analysis in different tissues validated that ent-CPP is the sole precursor to all DAs biosynthesis, with AcKSL1, AcKSL2s and AcKSL3-1 responsible for C20 atisine and napelline type DAs biosynthesis, respectively. These data clarified the molecular basis for the C20-DAs biosynthetic pathway in A. carmichaelii and pave the way for further exploration of C19-DAs biosynthesis in the Aconitum species.